Examining the Association Between Affiliate Marketing, Customer Ratings, and Product Quality and Their Impact on Consumer Purchase Decisions in TikTok Shop - Rendi Adi Saputra; Muhammad Nur Fietroh (Al-Qalam Institue, 2025)
This study aims to examine the effects of Affiliate Marketing, Online Customer Reviews, and Product Quality on PVN shoes' purchase decisions on the TikTok Shop application. This research uses a quantitative, associative method, with a population of students from Sumbawa University of Technology who have purchased PVN shoes. Data were collected via questionnaires distributed directly to respondents, and purposive sampling was used to select 210 respondents. Data analysis was conducted using multiple linear regression, t-test, and coefficient of determination (R²) with the assistance of SPSS 26. The results indicate that (1) Affiliate Marketing has a significant positive effect on the purchase decision of PVN shoes, (2) Online Customer Reviews have a significant positive effect on the purchase decision of PVN shoes, and (3) Product Quality has a significant positive effect on the purchase decision of PVN shoes. These findings provide a conceptual framework for understanding the factors that influence purchase decisions.